2022
DOI: 10.3748/wjg.v28.i44.6230
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning insights concerning inflammatory and liver-related risk comorbidities in non-communicable and viral diseases

Abstract: The liver is a key organ involved in a wide range of functions, whose damage can lead to chronic liver disease (CLD). CLD accounts for more than two million deaths worldwide, becoming a social and economic burden for most countries. Among the different factors that can cause CLD, alcohol abuse, viruses, drug treatments, and unhealthy dietary patterns top the list. These conditions prompt and perpetuate an inflammatory environment and oxidative stress imbalance that favor the development of hepatic fibrogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Inflammation plays a key role in MASLD, underscoring the importance of pursuing strategies aimed at reducing it [ 49 , 50 ]. Lifestyle interventions, such as hypocaloric diets based on the Mediterranean pattern, are highly effective and result in a reduction in proinflammatory markers [ 51 ], such as leptin and RBP4, as our results showed.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays a key role in MASLD, underscoring the importance of pursuing strategies aimed at reducing it [ 49 , 50 ]. Lifestyle interventions, such as hypocaloric diets based on the Mediterranean pattern, are highly effective and result in a reduction in proinflammatory markers [ 51 ], such as leptin and RBP4, as our results showed.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, liver-related diseases persist in imposing a substantial social and economic burden on numerous countries, leading to the loss of numerous lives each year. 99 Most alterations in liver disease are ascribed to a prolonged state of inflammation and an imbalance in oxidative stress. This imbalance fosters the progression of liver fibrosis (HF), which can ultimately lead to cirrhosis, or HCC.…”
Section: Study Of Ai Application In Diagnosis Of Liver Diseasesmentioning
confidence: 99%
“…This imbalance fosters the progression of liver fibrosis (HF), which can ultimately lead to cirrhosis, or HCC. 99 Nowadays, ML plays a significant role in assessing the risks associated with liver diseases. Serra-Burriel and colleagues 100 developed an early LiverRisk score utilizing the results of six routine tests aspartate transferase, alanine transaminase, gamma-glutamyl transferase, glucose, cholesterol, and platelet count) along with patient age and gender information.…”
Section: Study Of Ai Application In Diagnosis Of Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps background levels of EPA and DHA or the response to these fatty acids will also vary within each subpopulation of subjects with diabetes. Future studies using machine-learning approaches, as demonstrated in other disciplines, in the context of experiments with EPA/DHA will assist in moving the field forward [41][42][43][44].…”
Section: Integration Of Differing Inputs Of Heterogeneity Will Requir...mentioning
confidence: 99%